Paired Associative Electroacupuncture and Transcranial Magnetic Stimulation in Humans - Huang, Yi; Chen, Jui-Cheng; Chen, Chun-Ming; Tsai, Chon-Haw; Lu, Ming-Kuei (Frontiers in Human Neuroscience, 2019)
Pairing transcutaneous electric nerve stimulation and transcranial magnetic stimulation (TMS) with specific stimulus-intervals induces associative motor plasticity at the primary motor cortex (M1). Electroacupuncture (EA) is an established medical technique in the eastern countries. This study investigates whether EA paired with TMS induces distinct M1 motor plasticity. Fifteen healthy, right-handed subjects (aged 23.6±2.0 years, 8 women) were studied. Two hundred and twenty-five pairs of TMS of the left M1 preceded by right EA at acupoint ‘Neiguan’ (Pericardium 6, located 2 decimeters proximal from the wrist wrinkle) were respectively applied with the interstimulus interval of individual somatosensory evoked potential N20 latency plus 2 ms (N20+2) and minus 5 ms (N20-5) with at least one-week interval. The paired stimulation was delivered at a rate of 0.25 Hz. Sham TMS with a sham coil was adopted to examine the low-frequency EA influence on M1 in eleven subjects. M1 excitability was assessed by motor-evoked potential (MEP) recruitment curve with five TMS intensity levels, short-interval intracortical inhibition (SICI), intracortical facilitation (ICF) and cerebellar inhibition (CBI) at the abductor pollicis brevis (APB) muscle of the right hand before and after the EA-M1 PAS. In addition, median nerve somatosensory-evoked potentials (SSEP) and H-reflex were respectively measured to monitor somatosensory and spinal excitability. The MEP showed significantly facilitated after the sham EA-M1 PAS while tested with 80% of the TMS intensity producing on average 1mV amplitude (i.e. MEP1mV) in the resting APB muscle. It was also facilitated while tested with 90% MEP1mV irrespective of the stimulation conditions. The SSEP showed a higher amplitude from the real EA-M1 PAS compared to that from the sham EA-M1 PAS. No significant change was found on SICI, ICF, CBI and H-reflex. Findings suggest that repetitive low frequency EA paired with real TMS did not induce spike-timing dependent motor plasticity but EA paired with sham TMS induced specific M1 excitability change. Complex sensory afferents with dispersed time locked to the sensorimotor cortical area could hamper instead of enhancing the induction of the spike-timing dependent plasticity in M1.